Republic of Poland : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Poland. (IMF Staff Country Reports; Country Report ;, 2021)
After a long period of uninterrupted growth, Poland is experiencing a pandemic-induced recession, though strong policy actions have limited the damage. The economy rebounded strongly in the third quarter of 2020, but the second wave of the virus has delayed the recovery. A strong and effective policy response has supported economic activity and prevented destructive losses of employment and bankruptcies. Following the recession in 2020, Poland is well positioned for recovery. The pandemic will remain a constraint until the assumed administration of vaccines over the course of 2021. Resiliency in the corporate sector and labor markets, aided by strong policy support, should foster a strong rebound. Sizeable new EU grants would also facilitate an increase in investment and boost growth. The course of the pandemic and ultimate success of vaccines remains a fundamental risk.